Pengaruh Model Pembelajaran Discovery Dengan Bantuan Phet Terhadap Hasil Belajar Siswa - Kadek Ayu Kartika Septiana; Trisna Rukhmana; Moh Solehuddin; Joni Wilson Sitopu; Nofri Yudi Arifin; Okta Veza (Journal on Education, 2023)
This research is an experimental research which aims to find out whether there is an effect of the PhET Assisted Discovery Learning Model on the achievement of Class VIII Students on Straight Line Equations Material at SMP Negeri 36 Kerinci. The hypothesis in this study is that there is an influence of the PhET Assisted Discovery Learning Model on the Achievements of Class VIII Students on Straight Line Equations Material at SMP Negeri 36 Kerinci. This type of research is experimental research by providing different treatment to the experimental class and control class in mathematics learning. The population in this study was class VIII SMP Negeri 36 Kerinci for the 2022/2023 academic year, which consisted of 70 people. Then the experimental class and control class were determined randomly, which assigned class VIII B as the experimental class and class VIII C as the control class. The instrument used in this research is an objective test in the form of multiple choice. Before the test was given, it was first tried out in class VIII A of SMP Negeri 7 Kerinci for the 2022/2023 academic year. The hypothesis test used in this study was the t-test, but previously the normality test and variance homogeneity test were carried out. From the results of the t-test, the value of tcount = 2.66 and ttable = 1.678. This means that tcount > ttable so that H1 is accepted and H0 is rejected. From this calculation, it can be concluded that there is an influence of the PhET Assisted Discovery Learning Model on the Achievements of Class VIII Students on Straight Line Equations Material at SMP Negeri 36 Kerinci at the 95% confidence level.